Special Issue "Ethnopharmacology in Latin America" - Angel Josabad Alonso-Castro (MDPI AG, 2023)
Latin America is a multicultural region encompassing 43 countries, with 665 million inhabitants with a mean age of 31 years old, 84% of whom live in urban areas [...]